Предмет: Алгебра, автор: diananv

Найдите значение выражения  (frac{5b}{8a}- frac{8a}{5b}  ) * frac{1}{5b+8a}, при a= frac{1}{4}, b= frac{1}{9}

Ответы

Автор ответа: vladgushchin9
0
( frac{25b^{2} }{40ab} - frac{64a^{2} }{40ab} )* frac{1}{5b+8a} = frac{(5b-8a)(5b+8a)}{40ab} * frac{1}{5b+8a} = frac{5b-8a}{40ab}
если а= frac{1}{4} , b= frac{1}{9} , то<br />[tex] frac{(5a-8b)}{40ab} = frac{5* frac{1}{4}-8* frac{1}{9}  }{40* frac{1}{4} * frac{1}{9} } = frac{ frac{5}{4} -  frac{8}{9} }{40* frac{1}{36} } =   frac{ frac{13}{36} }{ frac{40}{36} } = frac{13}{40}
Похожие вопросы